2017
DOI: 10.1038/s41370-017-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality at an electronic cigarette (Vaping) convention

Abstract: E-cigarette (vaping) conventions are public events promoting electronic cigarettes, in which indoor use of e-cigarettes is allowed. The large concentration of people using e-cigarettes and poor air ventilation can result in indoor air pollution. In order to estimate this worst-case exposure to e-cigarettes, we evaluated indoor air quality in a vaping convention in Maryland (MD), USA. Real-time concentrations of particulate matter (PM 10 ) and real-time total volatile organic compounds (TVOCs), CO 2 and NO 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
7
29
0
Order By: Relevance
“…It has been found that during use, e-cigarettes produce PMs and moreover PM10 was almost made of PM1 size fraction [3]. There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211]. Analyses of the health risk of e-cigarette use for bystanders, i.e., passive smoking, indicate that exposure may be associated with irritation of the respiratory tract, systemic effects of nicotine action and increased risk of tumors [212].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 56%
“…It has been found that during use, e-cigarettes produce PMs and moreover PM10 was almost made of PM1 size fraction [3]. There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211]. Analyses of the health risk of e-cigarette use for bystanders, i.e., passive smoking, indicate that exposure may be associated with irritation of the respiratory tract, systemic effects of nicotine action and increased risk of tumors [212].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 56%
“…More recently, questions of second hand exposure to e-cigarette vapor have arisen. While some studies of simulated indoor air quality with ENDS have found no significant levels of chemicals in the environment (122), a non-simulated real life evaluation of indoor air quality at a vaping convention found high levels of air nicotine, particulate matter, total volatile organic compounds (TVOCs), and carbon dioxide in the air that raises concerns for workers and others exposed to second hand vapor (123). Serum cotinine levels in non-smokers from e-cigarette vapor were comparable to those exposed to second hand cigarette smoke in a recent study (124).…”
Section: Pollution and Air Qualitymentioning
confidence: 99%
“…The indoor aerosol size distributions generated by vaping (Schripp et al 2013;Schober et al 2014) as well as the composition of polycyclic aromatic hydrocarbons (McAuley et al 2012;Schober et al 2014;O'Connell et al 2015) have also been considered in these approaches. Other studies have been concerned with the nicotine concentrations (McAuley et al 2012;Schripp et al 2013;Czogala et al 2014;Ballbè et al 2017;Schober et al 2014;O'Connell et al 2015;Maloney et al 2015;Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%